Impact of electric vehicles on the operation of the Sri Lankan power system - Jayasinghe, D.H.G.A.E.; Wijekoon, R.; Ekanayake, J. (Ceylon Journal of Science, 2018)
It is anticipated that with the global trend towards decarbonizing the transport sector, depletion of fossil fuel resource and due to many other technical factors, Electric Vehicles (EVs) will increase in the car market in the future. The charging of a large number of EVs poses various technical challenges and requires special integration measures for power system operation. It is anticipated that depending on the charging regime EV will increase the operating reserve requirements. Quantifying the extent of incremental reserve requirement is vital for secure operation of the power system. This paper focuses on a methodology to estimate the regulating reserve requirement to compensate for the variations in the system load and EVs. Two different EV uptakes and two different charging regimes were considered. From extensive simulations studies it was found the increase in the regulating reserve is minute for the two scenarios considered. However, the long term scenario exhibits an increase in the regulating reserve thus alarming about a possible future issue with more EVs
Keywords: Electric Vehicles; Regulating reserve; Operational flexibility